Psychological Guidance of the Socialisation Process of Gifted Students using Information and Communications Technology Means - Androsovych, Kseniia A.; Rudyk, Yaroslav M.; Melnyk, Maryna Yu.; Kovalova, Oksana A.; Yakymova, Iryna O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: The purpose of this article is to substantiate the psychological conditions that determine the content, forms, ways of organising, and promoting the process of socialisation of gifted students. Background: The success of modern man largely depends on his socialisation – the ability to see and understand others, analyse the course of events, to capture the prospects for development. Therefore, the key competencies include, among others, information and communication and social as those that ensure the successful acquisition of knowledge throughout life and entry into society. Method: A set of methods was used in the study: analysis, synthesis, generalisation, and systematisation of scientific data, observations, questionnaires, document analysis, methods of mathematical data processing. An online testing platform was developed to conduct a survey of students. Results: The authors proposed and implemented a project aimed at providing psychological and pedagogical support to gifted students; to provide the teaching staff with the necessary knowledge and skills to work with gifted children, to encourage participants in the educational process to use information and communications technology tools in educational activities. A model of psychological support and accompaniment of participants in the educational process has been developed. Conclusion: The experiment showed positive changes in socialisation in the experimental group in relation to the control group at a significant level. The findings of the study give grounds to conclude that the proposed author’s comprehensive approach promotes the socialisation of gifted students.